Modeling and Parameter Extraction of PV Cell Using Single- and Two-Diode Model - Benabdelkrim, B; Benatillah, A (جامعة الوادي - university of el oued, 2017)
Photovoltaic modules operate under a large range of conditions. This combined with the fact that manufacturers provide electrical parameters at specific conditions (STC). The present study proposes a comparison between single and double diode models of solar PV system and ensures the best suited model under specific environmental condition for accurate performance prediction. An important feature of these models is that its parameters can be determined using data commonly provided by module manufacturers on their published datasheets. Accurate determination of these parameters which arose from a diversification of models and methods dedicated to their estimations is still a challenge for researchers. In this paper the single and two diode models have been studied by mathematical methods based on simulated Newton-Raphson iteration method. Newton-Raphson iteration method is solved by MATLAB simulation
Article
Keywords: PV Module; Single-diode model; Two diode model; Performance I–V Curves, Parameter Extraction